2015
DOI: 10.3892/or.2015.3882
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 expression pattern and TERT mutations in tumors of the vulva

Abstract: Malignant tumors of the vulva account for only 5% of cancers of the female genital tract in the USA. The most frequent cancers of the vulva are squamous cell carcinoma (SCC) and malignant melanoma (MM). Little is known about the genetic aberrations carried by these tumors. We report a detailed study of 25 vulva tumors [22 SCC, 2 MM, 1 atypical squamous cell hyperplasia (AH)] analyzed for expression of the high-mobility group AT-hook family member genes HMGA2 and HMGA1, for mutations in the IDH1, IDH2 and TERT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…HMGA2 is a member of the highmobility group of AT-hook proteins, which are expressed during embryonic development [35] as well as in different tumors (e.g. squamous cell carcinoma and malignant melanoma [36]). While only a few samples showed a TERT promoter mutation [36], it is still unclear if there is an association between HMGA2 expression and TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…HMGA2 is a member of the highmobility group of AT-hook proteins, which are expressed during embryonic development [35] as well as in different tumors (e.g. squamous cell carcinoma and malignant melanoma [36]). While only a few samples showed a TERT promoter mutation [36], it is still unclear if there is an association between HMGA2 expression and TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors have previously been characterized for their genomic alterations and deregulation of gene expression [4, 5, 8]. Four samples of normal vulva tissue from healthy donors were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…On chromosome 3, a deletion of the fragile histidine triad ( FHIT ) gene in 3p14 was reported leading to downregulation of gene expression [5]. Lately, overexpression of the high-mobility AT-hook 2 ( HMGA2 ) gene, mapping on 12q14.3, was shown [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Telomerase reverse transcriptase (TErT), a catalytic subunit of telomerase that includes an rnA component (TErC), therewithal maintains the telomere homeostasis and chromosomal integrity (15). reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). This study attempted to investigate whether immunohistochemical expression of TErT differs in neoplastic and nonneoplastic pituitary tissues and aimed to investigate whether TErT expression is related to clinicopathological features of pituitary adenomas.…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
“…TErT expression is suppressed in normal adult somatic tissues, but it can be expressed in embryogenic tissues. reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). Thus, TErT activity in pituitary adenomas has been the subject of a few studies that showed contradictory results (3,16,21).…”
Section: Introductionmentioning
confidence: 99%